Manifestaciones mucocutáneas debidas a la infección por Mycoplasma pneumoniae. Reporte de 3 casos - Beatriz Di Martino Ortiz; Tatiana Moreno; Silvia Mancia; Gloria Galeano (Our Dermatology Online, 2015)
Mycoplasma pneumoniae, one of the most frequent agents of community-acquired pneumonia worldwide, can affect different organs besides the lung, causing skin lesions in 25% of patients. The spectrum of dermatological features include macules, papules, purpura, target lesions and even well stablished conditions as erythema multiforme, Stevens- Johnson's Syndrome and toxical epidermal necrolysis. We present 3 pediatric patients with erythema multiforme and toxical epidermal necrolysis in which Mycoplasma pneumoniae was considered as the etiological agent.